Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Chronic Kidney Disease (CKD), Di Ruang Interne Rsud Prof. H. Muhammad Yamin, S.H Pariaman - Syahren Febria Marsa; Mike Asmaria; Kheniva Diah Anggita; Aulia Asman (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
One of the non-communicable diseases (NCDs) is Chronic Kidney Disease. CKD is a global health problem with an increasing prevalence and contributes significantly to high morbidity and mortality rates. According to the World Health Organization, CKD is one of the leading causes of death worldwide. In Indonesia, the prevalence of CKD based on the 2023 Indonesian Health Survey (SKI) was 0.18% or approximately 638,178 people, while in West Sumatra it reached 0.23% or 13,042 cases. At the local level, RSUD Prof. H. Muhammad Yamin, S.H Pariaman recorded an increase in CKD cases in the internal medicine ward, with 118 cases in 2023, 227 cases in 2024, and 327 cases in 2025. This study aimed to describe medical-surgical nursing care for patients with CKD. The method used was a case study with a descriptive approach involving one patient during five days of hospitalization. Data collection techniques included interviews, observations, physical examinations, and documentation studies. The results identified seven nursing diagnoses: impaired gas exchange, ineffective peripheral perfusion, hypervolemia, acute pain, sleep pattern disturbance, impaired skin integrity, and risk of decreased cardiac output. Nursing interventions provided included positioning, blood transfusion, circulation care, hypervolemia management, pain management, sleep support, skin integrity care, and cardiac care. The evaluation showed gradual improvement in the patient’s condition. It can be concluded that comprehensive, individualized, and continuous nursing care is effective in improving the condition of patients with CKD.